Penyelesaian Sengketa Lingkungan Non Litigasi Menurut Undang-Undang Nomor 32 Tahun 2009 - Agung Dwi Pranyoto (Peneliti.net, 2022)
Dispute resolution as mediation has been known since the first in Indonesia because the customary system in resolving cases always upholds deliberation to reach consensus through the traditional forums of each region in Indonesia. The Indonesian environment, which is bestowed by God Almighty to the Indonesian people, is a blessing from Him and its capabilities must be developed and preserved so that it can become a source and support for life for the Indonesian people and other creatures, for the sake of continuity and improvement of the quality of life itself. This study concludes that non-litigation environmental dispute resolution is considered more profitable because litigation in court takes a long time. By shortening the process, the impact of environmental damage can be more quickly addressed so that the ecosystem recovers quickly and social, economic and cultural life can run as it should.